Politics of Education: Multiculturalism Practice in Universitas Muhammadiyah Kupang, NTT. - David Efendi; Suswanta Suswanta (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
In Indonesia post authoritarian era, the education practice in many districts is facing several dynamics especially as logical consuqeunce from political decentralization including in education sector. There have been many horizontal conflicts in regions as political response in opposing central government acts to build local identity that frequently being clashed with racial/race/region based social conflict.This research aims to analyze the dynamic of higher education in Muhammadiyah university of Kupang (UMK) that managed by Muhammadiyah as private institution, to eventually understand how the design and practice of multiculturalism education in this Islam based university in Kupang. Of several FGD and interviews that we combine with political theory analysis about multiculturalism education, we find several conclusions that lead us to say that multicultural education design in UMK is not sufficient. Practice of respecting diversity in UMK is mostly based in individual awareness to naturally accept pluralism. This is also supported by family experience of student that since their early has been living in diversity.